Three-dimensional robust diving guidance for hypersonic vehicle. Issue 2 (15th January 2016) - Zhu, Jianwen; Liu, Luhua; Tang, Guojian; Bao, Weimin
Abstract: A novel three-dimensional robust guidance law based on H∞ filter and H∞ control is proposed to meet the constraints of the impact accuracy and the flight direction under process disturbances for the dive phase of hypersonic vehicle. Complete three-dimensional coupling relative motion equations are established and decoupled into linear ones by feedback linearization to simplify the design process of the further guidance law. Based on the linearized equations, H∞ filter is introduced to eliminate the measurement noises of line-of-sight angles and estimate the angular rates. Furthermore, H∞ robust control is well employed to design guidance law, and the filtered information is used to generate guidance commands to meet the guidance goal accurately and robustly. The simulation results of CAV-H indicate that the proposed three-dimensional equations can describe the coupling character more clearly than the traditional decoupling guidance, and the proposed guidance strategy can guide the vehicle to satisfy different multiple constraints with high accuracy and robustness.